Integrated Nutrient Management of Upland Taro in Assam - Saud, Bijit Kumar; Alam, S; Narzary, BD; S, Bora (JOURNAL OF ROOT CROPS, 2015)
Field experiments were conducted for three years on integrated nutrient management in upland taro at the Experimental Farm (Horticulture), Assam Agricultural University, Jorhat, Assam, during 2009-2012 as well as in the farmers’ field for on farm testing during 2011-2012. The experiment was conducted in RBD with nine treatments and three replications. The results showed that the treatments differed significantly. Application of vermicompost @ 1 t ha-1 + FYM @ 10 t ha-1 + 75% recommended dose of NPK (NPK @ 60:45:90) resulted in highest corm and cormel yield (17.07 t ha-1), number of cormels (12 cormels plant-1) and net return (` 3,34, 250 ha-1). Besides, the same treatment also performed well in the farmers’ fields with a mean yield of 16.70 t ha-1. The results of the present study showed the superiority of integrated nutrient management for profitable production of upland taro in Assam.